Industrial tourism as a chance for the diversification of the tourism of the Pécs-Mecsek region - Pintér, Réka; Csapó, János (Journal for Geography, 2016)
The present article intends to reveal the industrial tourism potential of the Pécs-Mecsek region in Hungary where we believe there is an adequate potential of the present industrial heritage but only a limited or rather poor utilisation is realised in the research area in this respect. The possible utilisation of the industrial heritage would be useful since the area is facing a stagnating tourism industry and position losses in the latter period so the authors believe that the chance for the renewal of tourism product development could also be provided by the industrial heritage tourism in the analysed region.